Sources and rates of nitrogen on the nutrition and productive performance of determinate growth habit snap bean - Ribeiro Barzan, Renan; Sandoval Contreras, Hector Augusto; Silvestre, João Pedro; Zucareli, Claudemir (University of Western Sao Paulo, 2024)
Snap bean is a vegetable crop presenting high requirements of mineral nutrients, such as nitrogen (N). However, studies on the response of this crop to N fertilization are scarce, mainly with determinate growth habit genotypes, making it difficult to manage the nutrient supply. The aim of this study was to evaluate the nitrogen nutrition and the productive performance of determinate growth habit snap bean as a function of N sources and rates. The experiment was carried out in pots, under greenhouse conditions, in a Red Latosol with 36.60 g dm-3 of soil organic matter content. The cultivar ‘Macarrão rasteiro’ TopSeedâ was grown in a completely randomized design at factorial scheme 3x4, with four replications. It was studied three sources of N (urea, ammonium sulfate and sulfammoâ) and four rates (0, 40, 80 and 120 kg N ha-1), applied 20% at sowing time, 40% at 12 days after emergence (DAE) and 40% at 20 DAE of the seedlings. It was evaluated the N content of the index leaf and the N accumulation in shoots, the plant height at the end of the cycle and the number, total fresh mass, mean fresh mass and mean length of pods. The N content of the index leaf and N accumulation in shoots were linearly increased by the N rates, regardless of the N source, while the plant height and the pod’s characteristics were influenced by none of the factors studied.